Answer:
[tex]y=Ce^{-x}[/tex]
Step-by-step explanation:
We are given that a differential equation
[tex]y'+3x^2y=0[/tex]
We have to find the general solution of given differential equation
General differential equation of first order and first degree is given by
[tex]y'+p(x)y=Q(x)[/tex]
Compare given differential equation with the general equation
Then , we get [tex]P(x)=3x^2[/tex],Q(x)=0
Integration factor=[tex]\int e^{3x^2dx}=e^{\frac{3x^3}{3}=e^x[/tex]
[tex]y\cdot I.F=\int Q(x)\cdot I.F+C[/tex]
Substitute the values then we get
[tex]y\cdot e^x=0+C[/tex]
[tex]ye^x=C[/tex]
[tex]y=Ce^{-x}[/tex]
Hence, the general solution of given differential equation
[tex]y=Ce^{-x}[/tex]